Etika Dan Spiritualitas Guru Pendidikan Agama Kristen Di Era Digital - Hendrik Legi; Gideon Wibiono; Antonius Wamo (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
The digital era has brought great changes in various aspects of life, including in the world of education. Christian Religious Education (PAK) teachers are required to not only master theological material, but also understand and integrate digital ethics and build a solid spirituality in the midst of cyber challenges. This article aims to examine the importance of ethics and spirituality in shaping the character of PAK teachers that are relevant to the needs of the times, as well as highlight the competencies that must be possessed in order to remain effective in educating the digital generation. Using the literature study method, this study examines theories about digital ethics, Christian spirituality, and educational principles based on the values of the Kingdom of God. The results of the study show that contemporary PAK teachers must be able to be role models in ethical behavior in virtual spaces, maintain integrity, respect digital rights, and live Christian values in every online activity. God's Word is the main basis for building ethical and spiritual sensitivity, as written in Romans 12:2 and Colossians 3:17. In addition, teachers are called to be light and salt in cyberspace, presenting a positive influence in the midst of information flows that are not always in accordance with Christian values. Through good digital competence, character strengthening, and deep spirituality, PAK teachers in the digital era are expected to shape students to become responsible, faithful, and integrity digital citizens. This research enriches the theoretical study of the role of Christian teachers in 21st century education.